Superstition and Its Role in Modern Business Management - J. A. Kovalchuk (Vestnik MGIMO-Universiteta)
Book Review: Crossman J. 2024. Superstition, Management and Organisations: Irrationality, Randomness, and Chaos in Decision Making. Palgrave Studies in Workplace Spirituality and Fulfillment. Palgrave Macmillan, Cham, 267 р. DOI: 10.1007/978-3-031-59020-7.